Expression of Plasminogen Activator Inhibitor 2 in the Adult and Embryonic Mouse Tissues - Kawata, Yoichi; Mimuro, Jun; Kaneko, Munekiyo; Shimada, Kazuyuki; Sakata, Yoichi (Thrombosis and Haemostasis, 1996)
We have studied the expression of plasminogen activator inhibitor 2 (PAI-2) in the adult mouse and during embryonic development using immunohistochemistry and the polymerase-chain reaction. Mouse PAI-2 mRNA was mainly expressed in the skin, bone-marrow, spleen, lung, thymus, and urinary bladder. Immunohistochemical studies suggested that PAI-2 was synthesized in macrophages and epithelial cells such as skin epithelial cells, transitional cells of the urinary bladder, and mesothelial cell of peritoneum and pleura. PAI-2 mRNA and antigen expression was observed only in the skin of 15 day-old mouse embryos. These data suggest that PAI-2 may play a role in protecting the mouse embryo from the protease attack in the amniotic fluid and also in maintaining and/or protecting the structure of various surfaces in the mouse.